“Ensayo de adaptabilidad y rendimiento de cuatro lineas promisorias de arroz (oryza sativa L.) en el sector pueblo libre valle del alto mayo-San Martín” - Barbarán Tello, Graciela (2008)
To identify the adaptability of 4 promising lines of rice with good yield potential, growíng season less than 140 days, good place, good abilíty to strong stems, resistant to attack major diseases and Pyricularia sp. virus White sheet, good quality milling and cooking and are suited to the climatic conditions of Alto Mayo. Ouring 2006, in the fields of Alto Mayo Special Project, founded by the producer Olegario Sanchez Segura, the Conquest Fiefds - Moyabamba developed this paper adjUSting lines, T1: CT15711-10-1-5-EP4-VC1 (PDA 1040} UQUIHUA/JUMA62 / / CT10473-3-1-15/SELVA HIGH T2: CT 15705-5 - 4 - 2- EP1-M CT7948-AM-3-1/CT 9852-3-2-1 21P-/ / CT79488-4-1P-2X, T3: l - 26 PROGRAMME CUBA, T4: IR 68427-76-1-2-2 IR 58029-180-2-3-3/IR 44624- 127-1 -2-2-3, T5: CAPIRONA, T6: INIA 14, T7: CONQUEST (INIA 507). We use a design a randomízed complete block with 7 treatments and 3 replicates. The treatment which won the best results was the T4: IR 68427-76-1-2-2 IR 58029- 180-2-3-3/IR 44624-127-1-2-2-3 performance with 7 166 Kg. I ha and with greater resistance to the attack of diseases in terms of witnesses commercial area INIA 14, INIA 507 (conquest), Capirona. Ouring the process of sifting diseases in the witness seedbed INIA 507 (conquest) rule for being susceptible to Rhizoctonía oryzae grade 9 and a percentage of teaf area affected by 100 %, by introducing severe infections and lesions on the leaves reaching top of the stem.